Spontaneous Pneumothorax in a Male High School Wrestler - Laura Breese; Sara Stiltner (Journal of Sports Medicine and Allied Health Sciences: Official Journal of the Ohio Athletic Trainers' Association)
OBJECTIVE/BACKGROUND A pneumothorax is the presence of air in the pleural space, it is a life threatening condition and can be classified as spontaneous, acquired, or by pathophysiology. This specific case presents the incident of a spontaneous pneumothorax in an adolescent population.